An In Vitro Usage of Origanum majorana Watery Extract as Inhibitory Antibacterial Component against Different Medically Important Bacterial Isolates - Zainab Adil Ghani Chabuck (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Origanum majorana demonstrates a broad spectrum of effectiveness against various diseases, exerting antimicrobial effects against different pathogenic microorganisms. The goals of this research are to provide light on how Origanum majorana extract inhibits human pathogenic bacteria, how it may prevent biofilm development, and how it affects bacterial adhesion. The antibacterial activity of the water-based Origanum majorana extract was assessed in this research using two different methodologies.